2019
DOI: 10.3390/ijms20020429
|View full text |Cite
|
Sign up to set email alerts
|

BAP1 Status Determines the Sensitivity of Malignant Mesothelioma Cells to Gemcitabine Treatment

Abstract: Malignant mesothelioma (MMe) is a cancer with poor prognosis and resistance to standard treatments. Recent reports have highlighted the role of the BRCA1 associated protein 1 gene (BAP1) in the development of MMe. In this study, the chemosensitivity of human mesothelioma cell lines carrying BAP1 wild-type (WT), mutant and silenced was analysed. The BAP1 mutant cells were significantly less sensitive than BAP1 WT cell lines to the clinically relevant drug gemcitabine. Silencing of BAP1 significantly increased r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 53 publications
3
35
0
Order By: Relevance
“…This is consistent with what already observed in ovarian and breast cancer patients with inherited mutations in BRCA1 and BRCA2 (55)(56)(57)(58). Conversely, BAP1 mutant mesothelioma cell lines resulted significantly less sensitive than BAP1 wild type cells to gemcitabine (59). In addition, the role of somatic BAP1 expression in MPM patients receiving chemotherapy still represents a matter of debate, with retrospective studies showing contradictory evidences (60,61).…”
Section: Targeted Therapiessupporting
confidence: 89%
“…This is consistent with what already observed in ovarian and breast cancer patients with inherited mutations in BRCA1 and BRCA2 (55)(56)(57)(58). Conversely, BAP1 mutant mesothelioma cell lines resulted significantly less sensitive than BAP1 wild type cells to gemcitabine (59). In addition, the role of somatic BAP1 expression in MPM patients receiving chemotherapy still represents a matter of debate, with retrospective studies showing contradictory evidences (60,61).…”
Section: Targeted Therapiessupporting
confidence: 89%
“…These data indicate that BAP1 regulates RRM2 levels during replication stress and that patients could be stratified for gemcitabine treatment, depending on BAP1 status. In a parallel study, Mutti’s team demonstrated that mesothelioma cells with functional BAP1 were more sensitive to gemcitabine treatment compared with cells bearing mutated and nonfunctional BAP1 . Together, these independent studies indicate that it may be possible to identify those patients with mesothelioma—and possibly patients with any cancer—who are more likely to respond to gemcitabine based on BAP1 status.…”
Section: Treatmentmentioning
confidence: 99%
“…RT is used as an adjuvant or neoadjuvant treatment in MPM, mainly in a palliative setting (8)(9)(10). As standard practice, patients undergoing an EPP receive adjuvant conventionally fractionated RT (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60) in the ipsilateral hemithorax area (18,19). In node-negative MPM patients, neoadjuvant therapy, based on intensity-modulated RT (IMRT) consisting of a fractionated irradiation of 5-6 Gy, is delivered before EPP (20)(21)(22).…”
Section: Radiotherapymentioning
confidence: 99%